KEHADIRAN SOSIAL BUDAYA ISLAM DI KABUPATEN WONOSOBO, JAWA TENGAH - Abdul Choliq Nawawi (Berkala Arkeologi, 1994)
This article explains the remains of Candi from the era of Ã‡ailendra in Kabupaten Wonosobo. It is known that the function of remains has changed in later era. It is become part of human grave structure such as jirat (tombstone), nisan (gravestone) and epitap board (short writing on gravestone or short statement written in the grave). These objects are in the grave complex during the presence of Islamic socio-culture in Kabupaten Wonosobo. The objects of Islamic socio-cultural heritage that have archaeological value are discovered in two districts, Kecamatan Kertek and Kecamatan Selomerto.